PENGARUH PEMBANGUNAN REAL ESTATE TERHADAP SEKTOR EKONOMI LOKAL : STUDI LITERATUR - Anggi Dwi Natalia; Nurul Hanifa (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Real estate development is a strategic sector closely linked to the dynamics of regional economic growth. Not only does it serve as a provider of housing needs, but it also plays a role in driving local economic activity through job creation, increasing land values, and the growth of the trade and services sectors. This article aims to comprehensively examine the impact of real estate development on the local economic sector through a literature study approach. The method used is a systematic literature review of national and international scientific articles obtained through the Google Scholar database. The results of the study indicate that real estate development generally makes a positive contribution to the local economy, particularly in increasing community income and diversifying livelihoods. However, real estate development also triggers the conversion of agricultural land and has the potential to cause social and environmental impacts if not managed sustainably. Therefore, integrated development planning is needed to ensure that the economic benefits of real estate development are balanced with social and environmental sustainability.